POLA KOMUNIKASI ORGANISASI TERHADAP KINERJA PEGAWAI DALAM MEMBERIKAN PELAYANAN SERTIFIKAT TANAH PADA DINAS PERTANAHAN KOTA MAKASSAR - Zobrina Syahwan , Tholita; Zelfia, Zelfia; Muttaqin, Andi (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
This study aims to find out how the performance of employees in providing land certificate services at the Makassar City Land Service so that efforts to fulfill the needs and requirements for satisfaction are realized in accordance with applicable regulations. This type of research is a qualitative descriptive method, namely research that aims to provide an overview of Employee Performance in Land Certificate Services at the Makassar City Land Office. The results of this study indicate that the performance of employees in providing land certificate services at the Makassar City Land Service is in accordance with performance indicators, namely, work quality, timing, initiative, ability and communication. However, in its implementation there are supporting factors where employees have carried out their duties and functions to the maximum extent possible seen from the quality and quantity of employee work achievements. while the inhibiting factor is the lack of facilities and infrastructure.